EVALUASI KUALITAS LAYANAN WEBSITE KIP KULIAH MENGGUNAKAN METODE E-GOVQUAL DAN IMPORTANCE-PERFORMANCE ANALYSIS (IPA) - Dorman, Adam; Fadhilah, Muhammad Afif; Adityawan, Rajendra Mahyaputra; Rizal, Muhammad (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2026)
The KIP Kuliah program is a strategic government initiative aimed at providing equal access to higher education, utilizing a website as its primary service gateway. However, user complaints regarding technical issues and service responsiveness frequently arise during peak registration periods. This study aims to evaluate the service quality of the KIP Kuliah website (kip-kuliah.kemdikbud.go.id) using the E-Government Service Quality (E-GovQual) method integrated with Importance-Performance Analysis (IPA). Data were collected via questionnaires from 60 active student users. IPA results indicate that the attributes of "Personal Data Security" (Trust) and "Help Response Speed" (Citizen Support) fall into Quadrant I (Top Priority), meaning user expectations are high while actual performance remains low. Supporting technical evaluation reinforces these findings with a mobile Largest Contentful Paint (LCP) score of 3.1 seconds, classified as slow. Managerially, this study recommends urgent improvements to the helpdesk features and the transparency of the privacy policy to enhance user trust.